839 Beta-Band Power Modulation in the Human Amygdala During a Go/No-Go Reaching Task. (April 2023) - Chung, Ryan; Martin del Campo-Vera, Roberto; Gilbert, Zachary; Tang, Austin M.; Cavaleri, Jonathan; Leonor, Andrea; Shao, Arthur; Tabarsi, Emiliano; Sundaram, Shivani; Kammen, Alexandra; Gogia, Angad S.; Liu, Charles Y.; et al.
Abstract : INTRODUCTION: The role of the amygdala in motor control is a developing area of investigation. Although classically known for its involvement in emotional processing, the amygdala has also been associated with modulating motor processing. For example, increases in the gamma frequency band (30-200 Hz) have been observed during volitional movements. However, the underlying neural mechanisms of amygdaloid motor movement and inhibition are not well-understood. METHODS: Nine patients with drug resistant epilepsy underwent implantation with stereoelectroencephalographic (SEEG) depth electrodes for seizure monitoring in the amygdala (5 bilaterally, 2 left unilaterally, and 2 right unilaterally). SEEG data were sampled throughout discrete phases of a Go/No-Go task (ITI, Fixation, Go/No-Go response), which required participants to touch a target or inhibit movement based on a colored cue. A Wilcoxon signed-rank hypothesis test was used to assess significant modulations of beta-band power between the response and fixation (baseline) phases of the task. RESULTS: In the Go condition, six out of seven patients with electrodes in the right amygdala had a significant decrease in beta-band power (p < 0.0479), and four out of seven in the left amygdala (p < 0.049). During the No-Go condition, seven out of seven patients with electrodes in the right amygdala displayed statistically significant increases of beta-band power when compared to the baseline period (p < 0.0451), and four out of seven in the left amygdala (p < 0.0137). CONCLUSIONS: This study reports beta-band power modulation in the human amygdala during voluntary movement in the setting of motor execution versus inhibition. This finding adds to previous studies in other brain areas that have linked beta-band power to motor control. The presence of beta-band power modulation in No-Go conditions suggests that the beta-band potentially plays a role in amygdaloid motor inhibition.